The endogeneity of business cycle synchronisation in SADC: A GMM approach - Ntokozo Patrick Nzimande; Harold Ngalawa (Cogent Economics & Finance, 2017)
Studies often conclude that the proposed Southern African Development Community monetary union would be disastrous and not optimal for all member countries. This is because of the observed low, and sometimes negative business cycle correlation amongst member countries. However, it has been demonstrated that the degree of synchronisation is not irrevocably fixed and is endogenous to certain economic factors. This study, therefore, sets out to investigate factors influencing business cycle synchronisation in the SADC region. More precisely, the study employs a generalised method of moments to investigate the influence of trade integration, financial integration, fiscal policy convergence, monetary policy similarity and oil prices (a proxy for global common shocks) on the degree of business cycle synchronisation. To conduct our analysis, we use data covering the period 1994-2014. In addition, we employ bilateral data as a way of getting around the problem of unavailability of aggregated regional data. The study finds trade, fiscal policy convergence and monetary policy similarity to have a sanguine impact on the degree of business cycle synchronisation. In addition, owing to their procyclical behaviour, it is observed that financial flows lead to diverging business cycles. Furthermore, the study finds that oil prices exert a negative impact on business cycle comovement in the SADC region. The study results have far-reaching policy implications for the proposed SADC monetary union. It is implied in the study findings that by stimulating trade and ensuring coherence in macroeconomic policies, SADC can move closer to being an optimal currency area.
Keywords: E32; F15 : J50; 330; business cycles; synchronisation; trade integration; financial integration; monetary union